Caracterização química do óleo essencial das folhas, galhos e frutos de Cinnamomum verum J. Presl (Lauraceae) - (:unkn) unknown (Museu Paraense Emílio Goeldi, 2020)
The essential oils of leaves, branches and fruits of a specimen of Cinnamomum verum J. Presl (Lauraceae) collected at Belém (Pará/Brazil), were extracted by hydrodistillation, and analyzed by gas chromatography coupled to mass spectrometry (GC/MS). Eugenol predominated in the essential oil of the leaves (64.2%), the branches displayed high levels of E-cinamila acetate (10.5%), E-cinamaldehyde (8.57%), and caryophyllene oxide (8.68%). The sesquiterpenes of the cadinan type, α-cadinol (8.72%), epi-α-cadinol (8.6%), δ-cadinene (6.81%) and γ-cadinene (6.48 %), were the main constituents of the essential oil of the fruits.
Chemical characterization of the essential oil from the leaves, branches and fruits of Cinnamomum verum J. Presl (Lauraceae)
Keywords: Cinnamomum verum; Canela; Eugenol; Cinnamon; CNPQ::CIENCIAS BIOLOGICAS::BOTANICA